Undergraduates performance on vaccine administration in simulated scenario - Lívia Cristina Scalon da Costa; Carolina Costa Valcanti Avelino; Lara Aparecida de Freitas; Aline Aparecida Machado Agostinho; Maria Betânia Tinti de Andrade; Sueli Leiko Takamatsu Goyatá (Associação Brasileira de Enfermagem, 2019)
ABSTRACT Objective: To evaluate the performance of nursing undergraduates on administration of vaccines in the vastus lateralis muscle of the thigh in children as a proposal of intervention, using simulated scenario, skill training and virtual learning environment. Method: Quantitative, quasi-experimental, pre and post-test, performed with 39 nursing students from a federal public university in 2017. The cognitive knowledge test and the Objective Structured Clinical Examination (OSCE) checklist were prepared, validated and applied before and after the intervention, adopting a level of significance of 95%. Results: The mean of the pre-test scores was 12.5 (SD= 2.56), post-test 17.4 (SD= 2.38), p <0.0001. The mean pre-OSCE score was 101.0 (SD= 30.46), post-OSCE 181.92 (SD= 12.04), p <0.0001. Conclusion: The effectiveness of the intervention proposal to increase knowledge and improve the performance of nursing students in administering vaccines to the vastus lateralis muscle of the thigh in children was evidenced.